Role of different echocardiographic modalities in the assessment of microvascular function in women with ischemia and no obstructive coronary arteries. Issue 8 (11th October 2022) - Jovanovic, Ivana; Tesic, Milorad; Djordjevic‐Dikic, Ana; Giga, Vojislav; Beleslin, Branko; Aleksandric, Srdjan; Boskovic, Nikola; Petrovic, Olga; Marjanovic, Marija; Vratonjic, Jelena; Paunovic, Ivana; Ivanovic, Branislava; et al.
Abstract: This review summarizes current knowledge about echocardiographic modalities used to assess microvascular function and left ventricular (LV) systolic function in women with ischemia and no obstructive coronary arteries (INOCA). Although the entire pathophysiological background of this clinical entity still remains elusive, it is primarily linked to microvascular dysfunction which can be assessed by coronary flow velocity reserve. Subtle impairments of LV systolic function in women with INOCA are difficult to assess by interpretation of wall motion abnormalities. LV longitudinal function impairment is considered to be an early marker of subclinical systolic dysfunction and can be assessed by global longitudinal strain quantification. Abstract : In women with ischemia and no obstructive coronary arteries (INOCA) stress echocardiography, coronary flow velocity reserve and left ventricular global longitudinal strain should be proposed as routine methods for evaluating microvascular function and systolic function impairment. These echocardiographic modalities are also important for determining the outcome of women with INOCA.